Enhancing company performance through strategic eWOM management: lessons from the Langkawi hotel sector / Elkhansa Medjedel ... [et al.] - Medjedel, Elkhansa; Wahab, Siti Norida; Sany, Salinda; Abdul Hamid, Abu Bakar; Othman, Norashida; Sakouchi, Ahmed Said (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
Company performance is crucial for sustained growth, profitability, and competitiveness. Positive electronic word-of-mouth (eWOM) on social networking sites (SNS) can significantly influence company performance by shaping brand perception and customer trust. This study examined the impact of strategic eWOM management on customers’ hotel booking intention in Langkawi and how it affected company performance. The Theory of Reasoned Action and the Information Acceptance Model acted as underpinning theories. The study employed a quantitative research methodology, utilizing an online survey questionnaire. 180 respondents were specifically selected from the population of Langkawi overnight travellers who possessed prior knowledge and familiarity with SNS. Findings indicated that eWOM quality exhibited the most prominent impact, followed by eWOM quantity and subjective norm. In contrast, eWOM credibility exerted a small impact on the intention of hotel booking. This study contributes to the existing literature by investigating the impact of strategic eWOM management on customers’ hotel booking intentions and its effect on the company’s performance. Practically, this study provides significant insights for hoteliers to leverage the significance of strategic eWOM as a strategic management tool to collectively shape reputation, customer perception, and operational success, influencing long-term sustainability and competitiveness in the digital era.